2023
DOI: 10.1002/anie.202314659
|View full text |Cite
|
Sign up to set email alerts
|

Bicyclic Guanidine Promoted Mechanistically Divergent Depolymerization and Recycling of a Biobased Polycarbonate

David H. Lamparelli,
Alba Villar‐Yanez,
Lorenz Dittrich
et al.

Abstract: We here report the organocatalytic and temperature‐controlled depolymerization of biobased poly(limonene carbonate) providing access to its trans‐configured cyclic carbonate as the major product. The base TBD (1,5,7‐triazabicyclo[4.4.0]dec‐5‐ene) offers a unique opportunity to break down polycarbonates via end‐group activation or main chain scission pathways as supported by various controls and computational analysis. These energetically competitive processes represent an unprecedented divergent approach to po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In order to establish the potential for recycling, poly­(carbonate) 8 of entry 11 (Table ) was subjected to depolymerization under TBD (1,5,7-triazabicyclo[4.4.0]­dec-5-ene) catalysis in toluene at 110 °C given its reported success in controlled PC degradation (Scheme a). , A reaction mixture of 8 in toluene was monitored, and NMR analysis demonstrated that after 7 h, full depolymerization of the starting material had occurred. From the crude product, finally cyclic carbonate-based product 16 was isolated in 67%, which corrected for a maximum carbonate content of 86% in 8 is a 78% “PC” recovery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to establish the potential for recycling, poly­(carbonate) 8 of entry 11 (Table ) was subjected to depolymerization under TBD (1,5,7-triazabicyclo[4.4.0]­dec-5-ene) catalysis in toluene at 110 °C given its reported success in controlled PC degradation (Scheme a). , A reaction mixture of 8 in toluene was monitored, and NMR analysis demonstrated that after 7 h, full depolymerization of the starting material had occurred. From the crude product, finally cyclic carbonate-based product 16 was isolated in 67%, which corrected for a maximum carbonate content of 86% in 8 is a 78% “PC” recovery.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the similarity between such monomers and the ones frequently utilized in the polymer/plastic-producing industries can more easily facilitate the transfer of biomass-based formulations to real-life applications. In this respect, it is not surprising that epoxy monomers have been central to many basic research studies and achievements and the identification of suitable renewable raw materials in this context remains rewarding. , Terpenes , and sugar-derived feedstock , have shown great promise as versatile precursors for epoxy monomers and related polycarbonate and polyester synthesis; fatty acid-chain based epoxides have also received considerable attention. …”
Section: Introductionmentioning
confidence: 99%
“…17–20 The advantages of its bio-origin, high level of functionality and depolymerization potential of PLC explain the increased efforts in using this polymer for various applications. 21–23 Moreover, recently it was reported that the estimated cost for PLC production is similar to the production cost of the petroleum-based polystyrene adding further to its potential use beyond academia. 24…”
mentioning
confidence: 99%
“…Catalytic ring-opening copolymerization (ROCOP) of LO and carbon dioxide is the main method for the synthesis of PLC , while ring-opening polymerization (ROP) of its trans -cyclic carbonate is also feasible. 23,25–28 In the ROCOP route, CO 2 offers a an additional renewable C1 building block for the synthesis of PLC being both highly available and cheap. A crucial parameter for the successful polymerization of PLC is the presence of a suitable catalyst due to the sterically demanding nature of the terpene oxide monomers.…”
mentioning
confidence: 99%